Estimating the size of the informal sector in Kenya - James Murunga; Moses Kinyanjui Muriithi; Nelson Were Wawire (Cogent Economics & Finance, 2021)
In Kenya, very little research has been carried out on the topic of the informal sector. This paper estimates the size of the Kenyan informal sector for the period 1970-2018. In light of our analysis of the stationary properties of the data, which suggests a mixture of I(0) and I(1) variables, this study specifies an Autoregressive Distributed Lag Model (ARDL), which is applied to variables that pose such attributes. In addition, the model is good for small sample size observation, a characteristic that is common among developing countries. Our estimates indicate that this sector is quite large and has grown over time to about 32% of the country's GDP or nearly one-third of the size of the recorded GDP. These results are consistent with the stylized fact about the Kenyan economy, in particular the large number of individuals employed in small businesses and trading as well as the number of tax returns filed on an annual basis versus the stated level of employment. The finding of a significant informal sector also has implications for the conduct of fiscal policy. The sector should not be wound abruptly since it provides employment to many Kenyans. The fiscal policy should aim at reducing the tax burden so that the participants in the informal sector gradually formalize their businesses.
Keywords: 330; Autoregressive Distributed Lag; currency; informal sector; Kenya; tax ratio